Development of Technical Specifications and Process System Requirements for the World’s Largest LH2 Refueling Station - Han Seojin; Kim Yeowon; Choi Yunjeong; Jo Seunghyeon; Maletzko Annabelle; Hwang Jihyun (E3S Web of Conferences, 2024)
Hydrogen is emerging as one of the premising energy sources to achieve carbon neutral society. To efficiently store and make use of the produced hydrogen by various methods, liquid hydrogen and liquid hydrogen refueling station (LHRS) are spotlighted as solutions for storage and utilization sector respectively. However, technical limitations of cryogenic pumps, heat exchangers and unconsolidated standards for LHRS led to hinder the wide spread of the stations. This paper reviews general technical specifications and safety standards of commercialized small-scale LHRS and suggests technical specifications and safety standards for large-scale LHRS. Especially, an application of separated cryogenic pumps and heat integration for the vaporizer specializes the designed station charging 1000kg of hydrogen per day in this paper from small-scale LHRS and other large-scale LHRS. The authors expect commercializing large-scale LHRS with the proposed technical specification and process system requirements to be able and the safety standards set for the designed station can contribute to the unification of world LHRS standards.